2016
DOI: 10.1371/journal.pone.0157083
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Untreated Psychosis in Chinese and Mauritian: Impact of Clinical Characteristics and Patients’ and Families’ Perspectives on Psychosis

Abstract: BackgroundDuration of untreated psychosis (DUP) is a potentially modifiable prognostic factor of course and prognosis of psychiatric disorders. Few studies have demonstrated that different cultural backgrounds or perspectives on psychosis may be important factors to the DUP. This study attempted to explore whether the DUP was different in Chinese and Mauritians and to clarify potential influencing factors to a long DUP (>3 months).Methods200 patients from China and 100 patients from Mauritius were enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 36 publications
0
23
1
Order By: Relevance
“…This idea was also used in other previous studies (Addington et al, ; Qin et al, ; Ran et al, ). Moreover, some studies found median DUP of 2 months (Kalla et al, ; Qiu et al, ; Schimmelmann et al, ), and 4 months (O'Donoghue et al, ); while other studies dichotomized DUP using the cut‐off point of 3 (Cotter, Zabel, French, & Yung, ; Devi Thakoor et al, ; González‐Valderrama et al, ). Thus, the cut‐off points of 2, 3, and 4 months were also considered in this study in order to see if results could be maintained.…”
Section: Methodsmentioning
confidence: 99%
“…This idea was also used in other previous studies (Addington et al, ; Qin et al, ; Ran et al, ). Moreover, some studies found median DUP of 2 months (Kalla et al, ; Qiu et al, ; Schimmelmann et al, ), and 4 months (O'Donoghue et al, ); while other studies dichotomized DUP using the cut‐off point of 3 (Cotter, Zabel, French, & Yung, ; Devi Thakoor et al, ; González‐Valderrama et al, ). Thus, the cut‐off points of 2, 3, and 4 months were also considered in this study in order to see if results could be maintained.…”
Section: Methodsmentioning
confidence: 99%
“…In Singapore, after adjustment, median and 75th percentile DUP were significantly higher among individuals of Indian compared with Chinese ethnicity (Basu, Subramaniam, Abdin, Poon, & Verma, 2015), whereas in Malaysia, DUP was longer for both Chinese and Indians than for indigenous people (Chee, Muhammad Dain, Abdul Aziz, & Abdullah, 2010). In a study conducted in China and Mauritius, the DUP did not differ between these populations, but there appeared to be less of a perception of stigma among the Chinese patients (Devi Thakoor et al, 2016). Two studies did not show differences in DUP between ethnic groups (Archie et al, 2010;Chong, Mythily, Lum, Chan, & McGorry, 2005).…”
Section: Ethnicity and Dupmentioning
confidence: 99%
“…Others examined DUP and socio-demographic factors (Apeldoorn et al, 2014;Burns & Kirkbride, 2012;Chee, Muhammad Dain, Abdul Aziz, & Abdullah, 2010;Hui et al, 2015;Valmaggia et al, 2015), DUP and pathways to care (Bhui, Ullrich, & Coid, 2014;Chong, Mythily, Lum, Chan, & McGorry, 2005), DUP and help-seeking (Bechard-Evans et al, 2007) or DUP and treatment delay (Boonstra et al, 2012;Morgan et al, 2005;Morgan et al, 2006), with at least 1 transcultural variable as a covariate in the analysis. One study explored DUP in populations in 2 different countries (Devi Thakoor et al, 2016).…”
Section: Study Aims and Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Economic conditions, racial and sociocultural factors, and public awareness on psychosis in developing countries also affect DUP. 27 Thus, DUP is a complex and multifaceted phenomenon that is associated with early-course illness development. 28 There is significant positive correlation between mean PAS scores and duration of untreated psychosis in affective psychosis (r= 0.646, p= 0.003) and there is no significant correlation between mean PAS scores and DUP in nonaffective psychosis (r= 0.395, p= 0.051) ( Table. 5a and 5b).…”
Section: Age Of Onset Dup and Premorbid Functioningmentioning
confidence: 99%